Comparative Outcomes Assessment of the C-Leg and X2 Knee Prosthesis. - Highsmith, Michael Jason (Comparative Outcomes Assessment of the C-leg & X2 Knee Prosthesis, 2012)
BackgroundThere are more than 300,000 persons in the U.S. living with transfemoral amputation (TFA). Persons with TFA use a knee prosthesis for gait and mobility. Presently, the C-Leg microprocessor knee prosthesis is the standard of care. C-Leg has significantly improved safety and cost efficacy and has created modest gains in gait efficiency. Recently, a new prosthesis has introduced a new sensor array and processor that reportedly improves knee motion, stair function and standing stability. Early claims of the reported functional benefits of the new Genium knee (formerly X2) have not been validated in a rigorous clinical trial. Therefore, the purpose of this project was to determine if the Genium knee improves safety, function and quality of life compared to the current standard of care (C-Leg).MethodsThe study is a randomized AB crossover with a control group. Subjects must have used (and still be using) a C-Leg for a minimum of 1yr prior to enrollment. Inclusion criteria beyond this are unilateral transfemoral or knee disarticulation amputation for any etiology, community level ambulation (Medicare level 3 or above), independent ambulation and ability to independently provide written, informed consent. Once enrolled subjects utilize their same socket but receive a study foot (Trias or Axtion). Subjects are randomly assigned to either stay with their C-Leg or be fit with a Genium knee. Subjects accommodate and test (A phase) then crossover to the other knee condition and repeat the testing (B phase). A follow up phase of the study beyond the B phase is ongoing to study longer term preference. For AB assessment, three domains were assessed: Safety, function and quality of life. For safety, the PEQ-A survey of stumbles and falls, posturography (Biodex SD limits of stability and postural stability tests), 4 square step test and 2 minute ramp stand test were completed. For function, a series of timed walking tests, the amputee mobility predictor, kinematic gait assessment and physical functional performance-10 tests were conducted. For quality of life, the socioemotional and situational satisfaction domains of the population specific and validated PEQ (prosthesis evaluation questionnaire) were completed.ResultsSafety: Posturographic assessment revealed impairment between transfemoral amputees and non-amputees. Stumbles and semi-controlled falls decreased with Genium but were not significantly different. Four square step testing was significantly (p<=0.05) improved from 12.2s(3.3) to 11.1s(3.4) for the C-Leg and Genium respectively.Function: Kinematic asymmetry was minimally different between knee conditions. The AMP mean(SD) scores while subjects used C-Leg was 40.8(3.6; 33-45) and 43.3(2.6) [p<0.001]. PFP scores (cumulative), upper body function and endurance scores were improved with Genium compared with C-Leg at 9.1%(p=0.03), 8.7%(0.01) and 10.3%(0.04) respectively.Quality of Life: For quality of life, situational satisfaction favored Genium (p<0.001) which included subject's satisfaction with gait, training and quality of life in general.ConclusionC-Leg and Genium promote static weight bearing beyond asymmetric values reported in the literature. In terms of limits of stability, TFA's are clearly impaired, primarily over the amputated side posteriorly however the Genium seems to enable posterior compensations that coincide with multi-directional stepping improvements. Anteriorly, the C-Leg's toe triggering requirements seem to improve limits of stability but come at the cost of discomfort on ramp ascent. With regard to safety, it seems that both knee systems represent good options for the community ambulating TFA. The largest improvements with Genium were in the activities of daily living assessment; predominantly balance and upper body function. It seems that the combination of multi-direction stepping with starts and stops and stair ascent are key areas of improvement. In conclusion, the sensor array in the Genium knee prosthesis promotes improved function in activities of daily living. Specifically improved in this context were balance, endurance, multi-directional stepping, stair ascent and upper limb function in highly active transfemoral amputees.